Forbidden Fiji nights with her rival - Harroway, J. C. (Harlequin medical romance, 2024)
Trapped... with only their chemistry for company! Trauma surgeon Della has a love-hate relationship with her work rival and brother's best friend, Harvey. Three years ago, fresh from a messy divorce, she recklessly succumbed to the uncontainable need they shared. Then discovered Harvey had stolen a job out from under her! Now they're stuck working together in Fiji, and their verbal sparring is still as thrilling as it is infuriating. Della is acutely aware of how fine the line is between loathing... and longing. Is it simply a matter of time before they pick up where they left off...?